(untitled) (Global Journal of Management and Business Research, 2021)
With organizations racing towards achieving the largest market share and overcoming competitors, the human resource plays a pivotal role in enhancing the organization’s ability to achieve this goal through the talents employed and retained in the organization. The aim of this study is to investigate the impact of internal service quality on employee retention. The study population was represented by the employees in Kuwait Finance House, which is one of the most significant Islamic banks in Kuwait. The study sample was (612) employees, who formed a response rate (71.16%). Structural equation modeling (SEM) was used as a statistical method for data analysis and hypothesis testing. The results supported all hypotheses that indicated a positive impact of internal service quality and its dimensions on employee retention. Consequently, the study suggests that managers and leaders pay more attention to the psychological aspects of employees and provide an appropriate work environment that motivates them to stay in the organization.